The Impact Factors of Industry 4.0 on ESG in the Energy Sector - Nitlarp T. (2023)
Digital transformation refers to highly thought-out social, manufacturing, and organizational transitions driven by digital revolutions and emerging technologies. On the other hand, energy is a critical pillar of the economic growth of the country. Meanwhile, global interest in environmental, social, and governance (ESG) investment is growing. The conventional investment paradigm is being phased out in favor of investments that prioritize environmental, social, and corporate responsibility. The energy sector is one of the most significantly affected. Presently, the field of digital transformation is limited in its analysis about the sustainability factors and is still controversial, especially in the energy business. This paper identifies an in-corporation factor in Industry 4.0, taking into account the effect on ESG. The research papers and the World Economic Forum reports were investigated and identified the correlation factor using machine learning to analyze their contents. We spotlighted the documents relevant to the energy industry and sustainable development. To quantify the model, confirmatory factor analysis (CFA) is proposed to generate a valid model, followed by path analysis with latent variables to evaluate the structural equation modeling (SEM). The result provides the conceptual model with impact factors and their correlations. The goodness of fit value is acceptable for the agreed-upon condition, as well as a descriptive that incorporates Industry 4.0 and ESG in terms of business, industry, and ESG in relation to the energy sector’s key issues.